Draft Annual Plan 1982-83 Vol III Sectoral Programmes : Social and Community Services, Economic Services, General Services Government of Tripura - Planning Commission (Planning Commission, 1982)
Objectives and guidelines of the State’s Sixth Plan so farmer education is concerned are not different from the National Objective. It is the intention of the State Govt. to prepare a modest but realistic plan and to decentralise planning- process and its implementation. There is a need for involving the Panchayati's and blocks in this, regard.
Government of Tripura